REHABILITATION OF THE RAILWAY SECTION „KOS-TREBEŠICA“ IN MONTENEGRO - Zafirovski Zlatko; Knezevic Milos; Tesovic Ivana (My University, 2020)
This paper gives a brief overview of the works performed on the rehabilitation of the railway section “Kos-Trebešica”. The section extends from km 351 + 684.65 to km 358 + 428.35 for a total length of 6.75 km. The complexity of this section is essentially determined by the fact that it comprises 12 tunnels and six bridges, which is more than 50% of the whole section. During the rehabilitation, works on the substructure (landslide rehabilitation) and the superstructure, as well as some minor works on the overhead contact line and telecommunications were carried out. Rehabilitation works with a duration of 4 hours and 30 minutes a day, were carried out in difficult working conditions. Carrying out the works so that every day after their completion, passenger and cargo traffic could proceed unhindered was a true engineering challenge. The technology of the works, the materials used, as well as problems encountered during the implementation of the project, will be described shortly. From the organizational point of view, the works on the section were made even more difficult by the fact that there are no access roads and no service. The Contractor was a consortium of JV Strabag AG Austria and Crnagoraput AD Podgorica. The supervision of the works was carried out by the Institute of Civil Engineering Ltd. Podgorica. The Contracting Authority was the Directorate of Public Works Podgorica, and the End Recipient the Railway Infrastructure of Montenegro. The value of the works is 5,379,205.22 EUR. The contract was formed in accordance with the Fidic Red Book (1999 edition).
Keywords: Railway section „Kos-Trebešica“, rehabilitation works.